Inhibitive characteristics of cetylpyridinium chloride and potassium chromate addition on type A513 mild steel in acid/chloride media. Issue 1 (1st January 2017) - Fayomi, O.S.I.; Popoola, A.P.I.; Oloruntoba, T.; Ayoola, A.A.
Abstract: Linear polarization resistance and open circuit potential methods were used to assess the inhibitive and adsorption behaviour of Potassium chromate (K2 CrO4 ) and Cetylpyridinium chloride (CPC) on mild steel (MS) in HCl/NaCl solution. Results obtained show that K2 CrO4 and CPC inhibit MS significantly against massive degradation. However, under open circuit potential method, inhibition efficiency of K2 CrO4 decreased at higher concentration. The synergistic effect of both inhibitors is positive on the protection of mild steel against corrosion. An inhibitive efficiency of over 60% was recorded for the combined admixture. Morphological study showed that the exposed steel with the presence of K2 CrO4 and CPC possess some corrosion product with lesser pitting effect compare to unprotected steel with severe surface deterioration and uniform corrosion degradation. The corrosion inhibition performance of K2 CrO4 and CPC on mild steel surface was found to follow Langmuir adsorption isotherm model.